PRODUÇÃO LACRIMAL E DENSIDADE DE CÉLULAS CALICIFORMES CONJUNTIVAIS EM CÃES DA RAÇA SHIH-TZU - ALINE MARIA VASCONCELOS LIMA; NILO SÉRGIO TRONCOSO CHAVES; ANDRÉIA VITOR COUTO DO AMARAL; JÚLIA DE MIRANDA MORAES; CARLOS EDUARDO FONSECA ALVES (Ciência Animal Brasileira, 2011)
This study aimed to evaluate the Shih Tzu tear production quantity and quality, in order to compare it with tear production of different breeds previously described. The tear production quantitative evaluation was performed in 35 animals, by Schirmer tear tests 1 and 2 (STT-1 and STT-2), in absence or presence the local anesthetic ,respectively. Regarding the mucin tear layer, a qualitative tear production evaluation was performed in 1 5 animals through conjunctival goblet cell density (CGCD) analysis. The mean values obtained to STT-1 were 19.66 ± 7.30 and 21 .97 ± 5.69 for left eye LE) and right eye (RE), respectively. The mean values obtained toSTT-2 were 10.71 ± 6.10 and 9.14 ± 4.78 for LE and RE, respectively. Both STT-1 and STT-2 values found to the Shih Tzu dogs are within tear production standards of other breeds previously described. The mean CGCD found to LE was 13.64 ± 3.44, and to RE it was 13.64 ±4.07. These values are lower than those described for other breeds